Child Poverty, Evidence and Policy Mainstreaming Children in International Development - Jones, Nicola (Policy Press, 2011)
This book is about the ideas, networks and institutions that shape the development of evidence about child poverty and wellbeing, and the use of such evidence in development policy debates.